Benthische Foraminiferen in der Northeastwater-Polynaya, Europäisches Nordmeer - Ahrens, Michael J. (1994)
During cruise ARK IX/2+3 of R.V. "Polarstern" (15. May-4.Aug. 1993) to the waters of the Northeastwater (NEW) Polynya (80°N, 15°W), the colonization pattern of live (rose-bengal) stained benthic foraminifera (>63 μm) was investigated. The purpose of the investigation was to describe the hitherto little known biofacies in the region, and, furthermore, to observe, in which manner the assumed high production system of the polynya influences the foraminifera community on the sea floor. For the latter purpose, faunal data was compared with environmental parameters. On 19 stations (depths: 170-500 m), over 60 species were identified, of which on average 12 species contributed over 90 % of the total living numbers. The species assemblage was dominated by Elphidium excavatum, Cassidu/ina teretis, /slandiella islandica, Nonion Jabradoricum, Labrospira jeffreysii (orTrochammina nana), Labrospira crassimargo and Textularia spp. and showed general similarities to other arctic shelf regions. Calcareous foraminifera contributed approximately 60 % of the total living numbers, while the remainig 40 % were agglutinated (arenatious) forms. Foraminifera were counted in 3 size fractions (63-125 μm, 125-250 μm amd >250 μm). About 70 % of all individuals were found in the smallest size fraction (63-125 μm), about 25 % in the medium fraction (125-250 μm). Living individual numbers (>63 μm) in the uppermost sediment layer ranged from 67 to 507 ind/10 cm3, averaging about 200 ind/10 cm3, and decreased exponentially into deeper sediment strata. 5 cm into the sediment, living numbers were less than 1O % of surficial population densities. In addition, species composition changed and diversity decreased with sediment depth. lt was possible to distinguish between species with population maxima in the uppermost sediment layer ("epifaunal") and species with population maxima in deeper sediment layers ("infaunal"). Cores were analyzed to a maximum depth of 5 cm and it was assumed that deeper strata contained merely negligible numbers ...